The Relationship Between the Use of TikTok and PjBL Models with Music Learning Outcomes - Maharani, Meike Dwi; Nurharini, Atip (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2024)
This research explores the relationship between using TikTok as a learning medium and the Project Based Learning model with music learning outcomes. With the growing popularity of TikTok among children, this research aims to understand how the social media platform can be used effectively in an educational context, particularly in music learning. This study aims to determine the relationship between the use of TikTok and the project-based learning model with the learning outcomes of music art of grade IV students at SD Gugus Kemuning, Ngaliyan District. This research was a type of correlational research with a population of 306 people and a sample of 122 people taken using the quota sampling technique. Data on the use of TikTok and project-based learning models were collected through questionnaires, while data on music learning outcomes were obtained through practical tests. Data were analysed using regression analysis. The results of data analysis show that the relationship between the use of TikTok and project-based learning models with music learning outcomes is 0.408 with a coefficient of determination of 16.6%, meaning that there is a significant relationship between the use of TikTok and project-based learning models with music learning outcomes. This research provides evidence that social media, when used wisely, can be a tool or medium to support education and increase student engagement in music learning.